A new valid shock absorbency test for third generation artificial turf - Nunome, H.; Suito, H.; Shinkai, H.; Ikegami, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
This study aims to re-examine how much the current mechanical testing procedure is valid to evaluate the shock absorbency of third generation artificial turf (3-g turf) and to establish a new testing procedure which precisely reflects the acute load by human sports action. The standard DIN test was conducted for the 3-g turfs with different infill rubber size and the number of layers. The baseline of the load of acute sports action was obtained from the ground reaction force of landing of 50 cm height with minimal shock attenuation. For reproducing the force similar to such hard landing, a testing rig was developed and several types of the 3-g turf with different infill and depth: sand 40 mm, rubber 40 mm, rubber 15 mm and sand/rubber 40 mm were tested. The standard test was found to be inappropriate to evaluate the shock absorbency of the 3-g turf, in particular for likely acute, high loading by human sports action. In contrast, the newly developed testing rig succeeded in illustrating the differences of shock attenuation properties between the 3-g turfs. The need of replicate high loading test using an alternative testing procedure was highlighted.